ADVANTAGES OF USING ELECTRONIC EDUCATIONAL RESOURCES IN THE PROCESS OF TEACHING SPECIAL SUBJECTS (Academia Science Repository, 2023)
This article discusses in detail how to achieve the effectiveness of the educational system of teaching special subjects. the process of how to facilitate the effective organization of the system using computer technologies in the educational system, as well as how to increase and strengthen the interest of the participants in science is the main goal of this article.